Properties of Urea-Doped Ice in the CRREL Test Basin - Hirayama,Ken-ichi (1983)
In the course of model tests with urea-doped ice in the CRREL Ice Engineering Facility test basin, the growth process and the physical and mechanical properties of the model ice were investigated. The parameters which were varied were: urea concentration in the tank water, air temperature during growth, growth duration, and tempering time. Uniformity of ice thickness and ice mechanical properties over the whole tank area were found to be satisfactory. The structure of the urea-doped ice was found to be similar to that of the ice except for a relatively thick incubation layer over a dendritic bottom layer. Empirical relationships were established between: ice thickness and negative degree-hours; mechanical properties and growth temperature, urea concentration, and ice thickness; and reduction in mechanical properties and tempting time. The results of the study are presented in charts which permit reliable scheduling of model tests with required ice thickness and ice flexural strength. (Author)